Uma arquitetura P2P baseada na hierarquia do endereçamento IP com roteamento unificado - Pinheiro, Marcos Cesar Madruga Alves (2006)
There are some approaches that take advantage of unused computational resources in the Internet nodes - users´ machines. In the last years , the peer-to-peer networks (P2P) have gaining a momentum mainly due to its support for scalability and fault tolerance. However, current P2P architectures present some problems such as nodes overhead due to messages routing, a great amount of nodes reconfigurations when the network topology changes, routing traffic inside a specific network even when the traffic is not directed to a machine of this network, and the lack of a proximity relationship among the P2P nodes and the proximity of these nodes in the IP network. Although some architectures use the information about the nodes distance in the IP network, they use methods that require dynamic information. In this work we propose a P2P architecture to fix the problems afore mentioned. It is composed of three parts. The first part consists of a basic P2P architecture, called SGrid, which maintains a relationship of nodes in the P2P network with their position in the IP network. Its assigns adjacent key regions to nodes of a same organization. The second part is a protocol called NATal (Routing and NAT application layer) that extends the basic architecture in order to remove from the nodes the responsibility of routing messages. The third part consists of a special kind of node, called LSP (Lightware Super-Peer), which is responsible for maintaining the P2P routing table. In addition, this work also presents a simulator that validates the architecture and a module of the Natal protocol to be used in Linux routers